ETUDE DE LA DISPONIBILITÉ DU PHOSPHORE ASSIMILABLE DES COMPOSTS DE DÉCHETS URBAINS DANS DEUX SOLS DIFFÉRENTS - Etsè, Aziable; Sanonka, Tchegueni; Kokou, Sabi; Magnoudéwa, Bodjona B.; Kokou, Djahini; Koffi, Kili A.; Gado, Tchangbedji; Gnon, Baba (European Scientific Journal, ESJ, 2014)
The availability of assailable phosphate in the compost soil depends on the mineralization of organic matter, the binding reactions of this element, the nature and quality of the compost, but also the nature of the soil and climatic conditions. The work undertaken in this study aims to study the availability of available phosphate of two organic amendments (compost household waste two (C1 and C2) and composted different under different conditions ages) in both soils (S1 and S2). The mass of 0.5 g of compost mixed with 50 g of soil 33 tonnes per hectare is incubated under controlled conditions for 90 days. The humidity is adjusted to 10% of the water holding capacity of the soil and the temperature at 28 ° C. Between the beginning and end of incubation (90 days), an increase of 30.11%, 53.85%, - 1.29% and 95.65% of the content of available phosphate is noted for the treatments S1C1 , S1C2, S2C1 and S2 C2 respectively. Furthermore, the increase of the content of available phosphate is more noticeable in the amended soils by C2 to the compost in soil amended with C1 compost and soil without addition of organic amendments. After three months of incubation, the amount of available phosphate different treatments showed the following descending order: S2C2> S2C1> S1C2> S1C1> S1> S2. Composts C1 and C2 also have an effect on pH, exchangeable cations (EC) and cation exchange capacity (CEC) of soils.